The Effect of Exchange Rate Fluctuations and Oil Prices on the Export-Oriented Industries of the Country's Capital Market (Case Study: Stock Companies of Petrochemical Industry) - Atarodi, Sanaz; Dehghan, Abdolmajid; Asgari, Mohammadreza (International Journal of Economics and Financial Issues, 2018)
Given that the real exchange rate in Iran has undergone several shocks due to policies for the uniformization of the exchange rate and the reduction of oil revenues, as well as price fluctuations, the study of these fluctuations on the stock market has beneficial results, in empowering investors and managers. Considering the importance of the petrochemical industry as a strategic activity in Iran's economy, this study examines the relationship between exchange rate fluctuations and oil prices with stock market price in Iran's petrochemical industry through seasonal data from petrochemical companies, accepted in the Stock Exchange, using the VECM method, during the period of 1992-2015. The results indicate that exchange rate fluctuations and oil prices have a positive relationship with the stock market prices of petrochemical industry. Keywords: Exchange Rate Fluctuations, Stock Market Price, Oil Price, Iranian Petrochemical Industry, Vector Error Correction Model (VECM) JEL Classifications: C58, E44, F31